Oxytocin Enhancement of Emotional Empathy: Generalization Across Cultures and Effects on Amygdala Activity - Geng, Yayuan; Zhao, Weihua; Zhou, Feng; Ma, Xiaole; Yao, Shuxia; Hurlemann, Rene; Becker, Benjamin; Kendrick, Keith M. (Frontiers in Neuroscience, 2018)
Accumulating evidence suggests that the neuropeptide oxytocin can enhance empathy although it is unclear which specific behavioral and neural aspects are influenced, and whether the effects are modulated by culture, sex and trait autism. Based on previous findings in Caucasian men, we hypothesized that a single intranasal dose of oxytocin would specifically enhance emotional empathy via modulatory effects on the amygdala in an Asian (Chinese) population and explored the modulatory role of sex and trait autism on the effects. We first conducted a double-blind, randomized between-subject design experiment using a modified version of the multifaceted empathy task (MET) to determine whether oxytocin’s facilitation of emotional empathy can be replicated in Chinese men (n = 60). To further explore neural mechanisms behind and potential sex differences, functional MRI and skin conductance measures were acquired in an independent experiment incorporating men and women (n = 72). Oxytocin enhanced emotional empathy across experiments and sex, an effect that was accompanied by reduced amygdala activity and increased skin conductance responses. On the network level oxytocin enhanced functional coupling of the right amygdala with the insula and posterior cingulate cortex for positive valence stimuli but attenuated coupling for negative valence stimuli. The effect of oxytocin on amygdala functional connectivity with the insula was modulated by trait autism. Overall, our findings provide further support for the role of oxytocin in facilitating emotional empathy and demonstrate that effects are independent of culture and sex and involve modulatory effects on the amygdala and its interactions with other key empathy regions.